2021
DOI: 10.3390/cancers13051170
|View full text |Cite
|
Sign up to set email alerts
|

ANO1 Expression Orchestrates p27Kip1/MCL1-Mediated Signaling in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a heterogeneous group of tumors that derive from the mucosal epithelium of the upper aerodigestive tract and present high mortality rate. Lack of efficient targeted-therapies and biomarkers towards patients’ stratification are caveats in the disease treatment. Anoctamin 1 (ANO1) gene is amplified in 30% of HNSCC cases. Evidence suggests involvement of ANO1 in proliferation, migration, and evasion of apoptosis; however, the exact mechanisms remain elusive. Aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Though the activation of the p-ERK pathway, SEMA3C promotes cervical cancer growth, which is related to poor prognosis ( Liu et al, 2019a ). ANO1 encodes a calcium-dependent chloride channel protein and commonly amplifies to facilitate several cancers’ progression, including ovarian ( Liu et al, 2019b ), prostate ( Liu et al, 2012 ), breast ( Britschgi et al, 2013 ), and head and neck cancers ( Filippou et al, 2021 ). After neoadjuvant chemoradiotherapy, the expression level of IGHG2 increased significantly in rectal cancer, indicating that IGHG2 was originally with a low expression in tumor cells and existed as a protective factor, which was consistent with our prognostic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Though the activation of the p-ERK pathway, SEMA3C promotes cervical cancer growth, which is related to poor prognosis ( Liu et al, 2019a ). ANO1 encodes a calcium-dependent chloride channel protein and commonly amplifies to facilitate several cancers’ progression, including ovarian ( Liu et al, 2019b ), prostate ( Liu et al, 2012 ), breast ( Britschgi et al, 2013 ), and head and neck cancers ( Filippou et al, 2021 ). After neoadjuvant chemoradiotherapy, the expression level of IGHG2 increased significantly in rectal cancer, indicating that IGHG2 was originally with a low expression in tumor cells and existed as a protective factor, which was consistent with our prognostic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, research on colorectal cancer found that cyclin D1 protein expression was positively correlated with ERK1/2 and ANO1.ANO1 inhibits G1 to S phase progression by down-regulating the expression of the ANO1, which is consistent with the decreased expression of cyclin D1 ( 28 ). Suppressing ANO1 expression also had significantly lower cyclin D1, leading to changes in p27 Kip1 distribution and correlated with a cell cycle arrest phenotype in HNSCC ( 8 , 73 ).…”
Section: The Mechanism Of Ano1 Involved In Cancermentioning
confidence: 96%
“…Out of 517 CGI methylation probes negatively correlated with nearby SV breakpoints, 50 involved genes positively correlated between mRNA and SV breakpoints (overlap p < 1E−4, chi-squared test), of which 21 CGI probes involved positive correlations at the protein level. Genes involving SV-associated lower CGI methylation with concordant protein and mRNA changes included NID2 50 and ANO1 51 (Fig. 5d ).…”
Section: Resultsmentioning
confidence: 96%